Language Development and the Ontogeny of the Dorsal Pathway - Friederici, Angela D. (Frontiers in Evolutionary Neuroscience, 2012)
In the lack of clear phylogenetic data on the neurobiological basis of the evolution of language comparative data across species and ontogenetic data from humans may inform us about the possible neural prerequisites of language. In the adult human brain the language-relevant regions in the frontal and temporal cortex are connected by different pathways: ventral and dorsal pathways. Ontogenetically, it is shown that newborns display an adult-like ventral pathway at birth. The dorsal pathway involving the arcuate fasciculus and the superior longitudinal fasciculus seems to display two subparts in the adult brain: one connecting the temporal cortex to the premotor cortex and one connecting the temporal cortex to Broca’s area. While the former subpart is present at birth, the latter develops much later and is even not fully matured at the age of seven years, an age when children still have problems in processing syntactically complex sentences. We therefore suggest that the mastery of complex syntax which is a core of human language crucially depends on the connection between the temporal cortex and Broca’s area.